Some Properties of Solutions to Multiterm Fractional Boundary Value Problems with p-Laplacian Operator - KumSong Jong; HuiChol Choi; KyongJun Jang; SongGuk Jong; KyongSon Jon; Ok Ri (Journal of Function Spaces)
In this paper, we study some properties of positive solutions to a class of multipoint boundary value problems for nonlinear multiterm fractional differential equations with p-Laplacian operator. Using the Banach contraction mapping principle, the existence, the uniqueness, the positivity, and the continuous dependency on m-point boundary conditions of the solutions to the given problem are investigated. Also, two examples are presented to demonstrate our main results.